1997
DOI: 10.1172/jci119156
|View full text |Cite
|
Sign up to set email alerts
|

Important role of tissue angiotensin-converting enzyme activity in the pathogenesis of coronary vascular and myocardial structural changes induced by long-term blockade of nitric oxide synthesis in rats.

Abstract: The long-term administration of N -nitro-L -arginine methyl ester (L-NAME), an inhibitor of nitric oxide synthesis, produces coronary vascular remodeling and myocardial hypertrophy in animals. This study used a rat model to investigate the role of angiotensin I converting enzyme (ACE) in the pathogenesis of such changes. We studied the following groups, all of which received drug treatment in their drinking water: untreated controls, and those administered L-NAME, L-NAME, and an ACE inhibitor (ACEI), and L-NAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
232
4
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(258 citation statements)
references
References 42 publications
(60 reference statements)
16
232
4
6
Order By: Relevance
“…4,5 The structural changes consistently observed after long-term NOS inhibition include vascular hypertrophy and adventitial collagen deposition. 6 A number of factors may contribute to this pathology, including increased local vascular expression of ACE, 6 endothelin production, 7 and the induction of type I collagen expression. 8 Conversely, ACE inhibition and endothelin antagonists have been shown to prevent hypertension and perivascular fibrosis in L-NAMEtreated animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The structural changes consistently observed after long-term NOS inhibition include vascular hypertrophy and adventitial collagen deposition. 6 A number of factors may contribute to this pathology, including increased local vascular expression of ACE, 6 endothelin production, 7 and the induction of type I collagen expression. 8 Conversely, ACE inhibition and endothelin antagonists have been shown to prevent hypertension and perivascular fibrosis in L-NAMEtreated animals.…”
mentioning
confidence: 99%
“…8 Conversely, ACE inhibition and endothelin antagonists have been shown to prevent hypertension and perivascular fibrosis in L-NAMEtreated animals. 6,8 Aside from the well-defined roles that endothelial NO plays in regulating vascular tone and structure, it has also been reported that NO suppresses plasminogen activator inhibitor-1 (PAI-1) expression in vascular tissue. 9 It was recently reported that long-term NOS inhibition induced vascular PAI-1 expression in rat models.…”
mentioning
confidence: 99%
“…These data on the ability of taxifolin to bring the ACE activity to the normal level have been obtained for the first time; however, it is possible to compare them with the influence of flavonoids on other manifestations of age-related vessel pathology or pathology caused by the NO synthase inhibitor or glucocorticoid hormones. As known, vessel remodeling in rats enhances with aging (Basso et al 2007) and as a result of the effect of the NO synthase inhibitor (Takemoto et al 1997;Katoh et al 2001). In these cases, pathological changes in vessels are caused by enhanced ACE activity because ACE inhibitors prevent vessel remodeling (Takemoto et al 1997;Katoh et al 2001;Basso et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As known, vessel remodeling in rats enhances with aging (Basso et al 2007) and as a result of the effect of the NO synthase inhibitor (Takemoto et al 1997;Katoh et al 2001). In these cases, pathological changes in vessels are caused by enhanced ACE activity because ACE inhibitors prevent vessel remodeling (Takemoto et al 1997;Katoh et al 2001;Basso et al 2007). Glucocorticoid hormones also increase the ACE activity in the aorta ), blood pressure (Saruta 1996), and the risk of CVD (Nashel 1986;Souverein et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation